Guidelines for Developing Standards for Exporting Halal Thai Poultry Products for Thai Entrepreneurs to Saudi Arabia After the Restoration of Thai-Saudi Relations - Maneewong, Napasswan; Aroman, Bandit (Thailand Islamic Journal, 2025)
Abstract This research was conducted with the following four key objectives: (1) to explore the various regulatory standards governing the export of poultry products from Thai enterprises to the Kingdom of Saudi Arabia, in accordance with Saudi import regulations (2) to investigate the halal production processes employed by Thai poultry producers for exports destined for the Saudi market (3) to analyze the opportunities, challenges, competitive advantages, and trade potential of Thai halal poultry products in Saudi Arabia; and (4) to develop strategic recommendations for enhancing Thailand’s halal poultry export standards to be fully aligned with Saudi Arabia’s import requirements. The study adopted a qualitative research methodology, utilizing in-depth interviews with scholars, subject matter experts, and business operators who have experience exporting poultry products from Thailand to Saudi Arabia. Moreover, this research underscores the importance of identifying emerging trade opportunities and leveraging Thailand’s unique product strengths—namely, its reputation for high-quality production and robust food safety practices. These elements can serve as key drivers in formulating a strategic framework for advancing the standards of Thai halal poultry exports, thereby enhancing their competitiveness in the global marketplace